(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Shchuka G. P. The content of training of tourism specialists in higher educational institutions of the Russian Federation and Ukraine: comparative analysis. In the article on the basis of the comparison, comparison, generalization of domestic and Russian standards for the preparation of bachelors and masters of tourism is determined by the General and specific in the content of the training of tourism specialists of this level, perspectives of introduction of separate elements of the experience of the Russian colleagues in the activity of the domestic educational institutions, implementing the training direction «Tourism».